THE PROBLEM OF UNSUFFICIENT ATTENDANCE PHYSICAL EDUCATION LESSONS - Nuriddinov Akhmad Muhammadievich; Berdirasulov Dilshod Kodirovich (Scholar Express Journals, 2022)
Physical culture is important for a developing organism. The article highlights the research results that can explain the reasons for the loss of students' interest in the physical education lesson.
Keywords: Student; Relevance Of Physical Culture; Secondary School Teacher; Questioning